Pregnancy rates in MGA-prostaglandin synchronized heifers bred at estrus or inseminated at fixed times - Smith, J.M.; Corah, L.R.; Lamb, G.C.; Spell, A.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The objective of this project was to study the effects on pregnancy rates of inseminating estrus-synchronize d heifers either at observed estrus or at a fixed time. In April, 1994, 574 yearling crossbred heifers, located on six Kansas ranches, were inseminated to achieve this objective. Her d size ranged from 38 to 293 head. The heifers were synchronized with the MGA-prostaglandin (PGF) system. Heifers were either inseminated 12 hr after the onset of estrus or, if not showing estrus, 72 hr after PGF. Pregnancy rates of 491 heifers bred on estrus averaged 56.6% (39.2 to 80.4%). Pregnancy rates for the 83 fixed-time-inseminated heifers average d 39.8% (15.6 to 56.5%) . Heifers that responded to the MGA-PGF synchronization system with a standing heat had higher pregnancy rates than those that were inseminate d at a fixed time. However, fixed-time inseminations used in conjunction with inseminations made at estrus increased the total number of heifers bred to proven AI sires.
Keywords: Beef; Heifer; Synchronization of estrus; Fixed-time insemination